Creation, validation, and reliability of a shooting simulator instrument for reaction time evaluation - Ellen dos Santos Soares; Sara Teresinha Corazza; Ana Carla Piovesan; Renato Preigschadt de Azevedo; Silvio José Lemos Vasconcellos
Abstract "Creation, validation, and reliability of a shooting simulator instrument for reaction time evaluation." The aim of this study was to develop, validate, and verify the reliability of a shooting simulator instrument for reaction time evaluation. 90 Santa Maria Air Base military personnel participated on the study. Software was developed for use with an electronic gun where participants performed two shooting task tests: simple reaction time and choice reaction time. The results of concurrent validity were satisfactory, no significant differences were found between the two instruments and good agreement was observed. The reliability results were significant in both tests. The instrument can be used for research purposes, or for the purposes of military training as a simple, low-cost tool involving speed, accuracy, and decision-making shooting tasks.